Multifunctional iron-biochar composites for the removal of potentially toxic elements, inherent cations, and hetero-chloride from hydraulic fracturing wastewater - Sun, Yuqing; Yu, Iris K M; Tsang, Daniel C W; Cao, Xinde; Lin, Daohui; Wang, Linling; Graham, Nigel J D; Alessi, Daniel S; Komárek, Michael; Ok, Yong Sik; Feng, Yujie; Li, Xiang-Dong (Environment international, 2019)
This paper evaluates a novel sorbent for the removal of potentially toxic elements, inherent cations, and hetero-chloride from hydraulic fracturing wastewater (FWW). A series of iron-biochar (Fe-BC) composites with different Fe/BC impregnation mass ratios (0.5:1, 1:1, and 2:1) were prepared by mixing forestry wood waste-derived BC powder with an aqueous FeCl3 solution and subsequently pyrolyzing them at 1000 °C in a N2-purged tubular furnace. The porosity, surface morphology, crystalline structure, and interfacial chemical behavior of the Fe-BC composites were characterized, revealing that Fe chelated with CO bonds as COFe moieties on the BC surface, which were subsequently reduced to a CC bond and nanoscale zerovalent Fe (nZVI) during pyrolysis. The performance of the Fe-BC composites was evaluated for simultaneous removal of potentially toxic elements (Cu(II), Cr(VI), Zn(II), and As(V)), inherent cations (K, Na, Ca, Mg, Ba, and Sr), hetero-chloride (1,1,2-trichlorethane (1,1,2-TCA)), and total organic carbon (TOC) from high-salinity (233 g L-1 total dissolved solids (TDS)) model FWW. By elucidating the removal mechanisms of different contaminants, we demonstrated that Fe-BC (1:1) had an optimal reducing/charge-transfer reactivity owing to the homogenous distribution of nZVI with the highest Fe0/Fe2+ ratio. A lower Fe content in Fe-BC (0.5:1) resulted in a rapid exhaustion of Fe0, while a higher Fe content in Fe-BC (2:1) caused severe aggregation and oxidization of Fe0, contributing to its complexation/(co-)precipitation with Fe2+/Fe3+. All of the synthesized Fe-BC composites exhibited a high removal capacity for inherent cations (3.2-7.2 g g-1) in FWW through bridging with the CO bonds and cation-π interactions. Overall, this study illustrated the potential efficacy and mechanistic roles of Fe-BC composites for (pre-)treatment of high-salinity and complex FWW.
Keywords: adsorpce; Adsorption; chemické látky znečišťující vodu; kationty; chloridy; hydraulické štěpení; oxidace-redukce; Cations; odpadní voda; Iron; Oxidation-Reduction; Chlorides; dřevěné a živočišné uhlí; železo; Charcoal; Wastewater; Hydraulic Fracking; Water Pollutants, Chemical